The China syndrome [videorecording] - Bridges, James; Douglas, Michael; Columbia Pictures (Culver City, Calif. : Columbia Tristar Home Entertainment, 2004)
It started as just another assignment. Reporter Kimberly Wells and cameraman Richard Adams were covering the daily routine at an Los Angeles power plant when the unthinkable occurred: a nuclear accident that could have wiped out Southern California. And Richard caught it all on tape. When their TV station refuses to air the footage, Wells and Adams recruit plant supervisor Jack Godell to expose the terrifying truth: the facility is a ticking bomb. But with millions of dollars at stake, company officials cannot let the story break. When the trio attempts to broadcast live from the plant's control room, the utility company does everything in its power to silence Godell permanently, as the world watches.
Originally released as motion picture in 1979.
Special features: Theatrical trailors, bios/filmographies and scene selection.
Associate producer, James Nelson ; executive producer, Bruce Gilbert.
Performers: Jack Lemmon, Jane Fonda, Michael Douglas.
DVD format.
Subtitles available in English, Spanish, Portuguese, Chinese, Korean and Thai.
Keywords: Television journalists -- Drama; Nuclear power plants -- Accidents -- Drama; Conspiracies -- Drama